Clients' reasons for prenatal ultrasonography in Ibadan, South West of Nigeria - Gbadamosi Sikiru A; Sogo Kayode; Kalejaiye Adegoke O; Adedokun Babatunde O; Marinho Anthony O; Morhason-Bello Imran O; Enakpene Christopher A; Awoyinka Babatunde S; Enabor Obehi O (BMC, 2009)
Abstract Background Prenatal ultrasonography has remained a universal tool but little is known especially from developing countries on clients' reasons for desiring it. Then aim was to determine the reasons why pregnant women will desire a prenatal ultrasound. Methods It was a cross-sectional survey of consecutive 222 women at 2 different ultrasonography facilities in Ibadan, South-west Nigeria. Results The mean age of the respondents was 30.1 ± 4.5 years. The commonest reason for requesting for prenatal ultrasound scans was to check for fetal viability in 144 women (64.7%) of the respondents, followed by fetal gender determination in 50 women (22.6%. Other reasons were to check for number of fetuses, fetal age and placental location. Factors such as younger age, artisans profession and low level of education significantly influenced the decision to check for fetal viability on bivariate analysis but all were not significant on multivariate analysis. Concerning fetal gender determination, older age, Christianity, occupation and gravidity were significant on bivariate analysis, however, only gravidity and occupation remained significant independent predictor on logistic regression model. Women with less than 3 previous pregnancies were about 4 times more likely to request for fetal sex determination than women with more than 3 previous pregnancies, (OR 3.8 95%CI 1.52 - 9.44). The professionals were 7 times more likely than the artisans to request to find out about their fetal sex, (OR 7.0 95%CI 1.47 - 333.20). Conclusion This study shows that Nigerian pregnant women desired prenatal ultrasonography mostly for fetal viability, followed by fetal gender determination. These preferences were influenced by their biosocial variables.